Pro-inflammatory cytokines and suicidal behavior among patients with bipolar I disorder. (June 2022) - Huang, Mao-Hsuan; Chen, Mu-Hong; Chan, Yee-Lam E.; Li, Cheng-Ta; Tsai, Shih-Jen; Bai, Ya-Mei; Su, Tung-Ping
Abstract: Objective: Suicidal behavior and different mood states of bipolar I disorder (BD) have been shown to be associated with dysregulated proinflammatory cytokines. Only a few studies have examined the association between inflammation and SB in BD, and the association between proinflammatory cytokines, SB, and cognitive deficits in patients with BD remains unclear. Methods: 77 patients with BD and 61 age-/sex-matched healthy controls were recruited. Patients were divided into two groups: with suicidal ideation (SI; n = 21) and no SI (n = 56). SI was defined by a score of ≥1 in item 10 of Montgomery Åsberg Depression Rating Scale. Levels of proinflammatory cytokines, including soluble interleukin-6 receptor (sIL-6R), soluble tumor necrosis factor-α receptor type 1 (sTNF-αR1), and C-reactive protein (CRP), were measured, and cognitive function was assessed using 2-back task and Go/No-Go task. Results: Patients with SI had higher levels of sTNF-αR1 than those without SI and the controls ( p = .004). BD patients with or without a history of suicide attempt had higher levels of CRP than the controls. SI was associated with serum levels of sTNF-αR1 and IL-6sR, even after additionally controlling for working memory and inhibitory control ( p < .05). Conclusion: This study indicates that serum levels of sTNF-αR1 have distinct differences between BD patients with or without SI, and our findings strengthen the hypothesis of a link between suicidal behavior and neuro-inflammation pathophysiology in BD. Highlights: BD patients with suicidal ideation (SI) had higher serum levels of sTNF-αR1 than controls and patients without SI. BD patients with/without history of suicide attempt had higher serum levels of CRP. Serum levels of sTNF-αR1 and sIL-6R were associated with SI in outpatients with BD. Proinflammatory cytokines may play an important role in the identification of suicide risk among patients with BD.